Compact filters with slot resonators and fast method of its analysis (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2016)
Introduction. The investigation of possibility of using the slot resonators in compact microwave filters with Chebyshev characteristic is the aim of the work. The constructions on the base of filters-prototypes with sections of length λ/16 with narrow rectangular slot resonators in microstrip line ground plane are considered. Main part. On the base of transmission line theory, the fast analyzing technique of such filters by means of ABCD-matrices is proposed (simple theory). The constructions of compact filters with using narrow rectangular slot resonators in microstrip line ground plane numerically analyzed and experimental measurement are proposed. Conclusion. According to the proposed technique, high-impedance sections of transmission line are replaced by physically realizable by width sections of microstrip transmission line with under placed rectangular slot resonators. As the result of filter elements optimization by scattering characteristics even more compact filters are obtained. They suppress parasitic pass-bands and have additional resonant frequencies in their pass-band.